Engaging Community Participation for a Sustainable Smoke Free Initiative - Sugiyo, Dianita (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Smoking prevalence in Indonesia remains high, and the percentage of young smokers increases by year, currently reaching 9.1% of the total youth in Indonesia. This global health problem is a severe non-communicable disease, which specifically targets adolescents. This observative research aims to investigate community involvement and multi-discipline coordination in intensifying the smoke-free village and campus, in order to support smoke-free policy. Multi-approach context was proven to deliver a significant impact on the implementation of the policy, which further provided the broad sectors with supports towards the same goal. Meanwhile, the community involvement gave an impression of the program to fasten the tie of social responsibility to succeed in the program. Multi-sector approach and the power of people empowerment have brought a powerful effect to public health. Thus, the same approach and system are essential to be introduced to the community and higher education institutions.